(untitled) (Psychology Travelogs, 2023)
The scientific views on the impact of social intelligence on the performance of initial activities in school age have been analyzed and summarized. It has been found that social intelligence directly participates in regulating social behavior, serves as a means of understanding social reality, combines and regulates cognitive processes related to the reflection of social objects, provides interpretation of information, understanding and predicting actions and behaviors of individuals, adaptation to different systems of relationships between people, and shows how a person interacts with the surrounding world, how to solve and overcome everyday problems, including communication with others. The peculiarities of social intelligence development in younger school-age children under different educational programs have been identified. A methodological and procedural complex of tasks aimed at studying social intelligence in younger school age has been created, psychodiagnostic tools and techniques for influencing social intelligence have been selected. The stages of socio-psychological training have been taken into account: preparatory, diagnostic, and analytical, in accordance with the tasks. It has been proven that there is a difference in the levels of development of social intelligence among students who study under different educational programs. The research has shown that there is indeed a trend in the development of the level of social intelligence among younger school-age children. We assume that this is associated with both the age dynamics of social intelligence and the specific features of different educational programs. The use of socio-psychological training for the development of social intelligence in younger students is proposed as methodological recommendations.